2021
DOI: 10.1177/00420980211026578
|View full text |Cite
|
Sign up to set email alerts
|

Housing wealth, mortgages and Australians’ labour force participation in later life

Abstract: In the life cycle model of consumption and saving, homeownership is an important vehicle for horizontal redistribution. Households accumulate wealth in owner-occupied housing during working lives before benefiting from imputed rent streams in retirement. But in some countries housing wealth’s welfare role has broadened as owners increasingly use flexible mortgages to smooth consumption during working lives. One consequence is higher outstanding mortgages later in life, a burden exacerbated by high real house p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…As shown in It may also be the case that because the superannuation guarantee system is maturing and working lives are extending later into the life course, current generations of homeowners may be more willing to carry debt into later life than before. Ong et al (2021) find that mortgagors in metropolitan areas reduce their odds of exiting the labour force by around 17 per cent for every $10,000 increase in mortgage debt secured against the home. The study presents some evidence supporting the idea that those planning to retire later are more willing to borrow against their homes.…”
Section: Home Ownershipmentioning
confidence: 92%
“…As shown in It may also be the case that because the superannuation guarantee system is maturing and working lives are extending later into the life course, current generations of homeowners may be more willing to carry debt into later life than before. Ong et al (2021) find that mortgagors in metropolitan areas reduce their odds of exiting the labour force by around 17 per cent for every $10,000 increase in mortgage debt secured against the home. The study presents some evidence supporting the idea that those planning to retire later are more willing to borrow against their homes.…”
Section: Home Ownershipmentioning
confidence: 92%
“…Homeownership provides older people with security of housing tenure and long‐term social and economic benefits and can be a key determinant of wealth and financial security in retirement (Parliament of Australia 2019; Productivity Commission 2013). Ong et al (2022) highlight that the housing wealth accumulated during working lives can be used to support well‐being in old age by hedging against rising rental costs and as a store of wealth that can be released to buffer against shocks. However, the rise of flexible mortgages and cost of living pressure have resulted in home equity being used to smooth income earlier in life, increasing numbers with outstanding mortgages closer to retirement which can result in debt‐induced extensions to working lives (Ong et al 2022).…”
Section: Housing In Retirement Planningmentioning
confidence: 99%
“…Yet the fulfilment of this aspiration has not been supported by changes to housing policies in the past few decades. Instead, policies operating alongside increased reliance on the market have widened inequalities in access to home ownership in Australia, with support for home ownership as an asset-based welfare strategy (Ong, Wood et al 2022), morphing into support for home ownership for already asset-rich Australians (Blunden 2016). Overwhelming government support in the housing domain is targeting towards tax concession for existing owners through capital gains tax concessions and negative gearing.…”
Section: Supporting Home Ownership In Australiamentioning
confidence: 99%
“…Even for those who do manage home ownership, Ong, Wood et al (2022) have noted increasing impacts of larger mortgage debts in delaying retirement. These authors found that higher levels of mortgage debt secured against the primary residence, particularly in urban areas and among men, was significantly prolonging working lives.…”
Section: Introduction: Pathways Into Home Ownership In the 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation